2006
DOI: 10.1243/095440505x32652
|View full text |Cite
|
Sign up to set email alerts
|

Review of Geometric Solutions for Milling Burr Prediction and Minimization

Abstract: In this paper a review of various methodologies for burr prediction and minimization in face milling is presented. In particular, the authors look into the geometric solutions employed, which typically consist of understanding and modifying tool engagement conditions. The extent of applicability of various approaches is discussed and the possible direction for future research is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Provision of a beveled work edge was reported to lower burr height noticeably in milling and drilling operations [12][13][14][15][21][22][23] due to gradually decreasing depth of cut and the reducing need of back-up support. Suitable tool path selection also reduces burr height [24]. Significant effect of different size of drills on burr formation was observed in some other works [14,15] under varying cutting conditions.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Provision of a beveled work edge was reported to lower burr height noticeably in milling and drilling operations [12][13][14][15][21][22][23] due to gradually decreasing depth of cut and the reducing need of back-up support. Suitable tool path selection also reduces burr height [24]. Significant effect of different size of drills on burr formation was observed in some other works [14,15] under varying cutting conditions.…”
Section: Introductionmentioning
confidence: 89%
“…formed in these tests as no back-up support material is available at the exit edge of the drilled hole. For this, shear plane is likely to have oriented to a negative direction facilitating formation of burr as shown inFigure 2[21,24]. When shear plane is oriented towards a negative plane, the chip is bent downwards and can be attached to the exit edge of workpiece forming a burr.…”
mentioning
confidence: 99%
“…Avila and Dornfeld 38 showed that tool geometry and in-plane exit angle Ψ have significant effects on burr size and edge breakout during the face milling of aluminum–silicon alloys (AlSi9Cu3 and AlSi7Mg). Tripathi and Dornfeld 49 reported the possibility of burr-free conditions when using diamond end mill tools at high cutting speeds. According to Gillespie and Blotter, 31 the use of sharp cutting edge tools with positive rake angle avoids built-up edge (BUE) formation, thus reducing the burr size.…”
Section: Factors Governing Milling Burr Formationmentioning
confidence: 99%
“…Avila and Dornfeld [37] showed that tool geometry and in-plane exit angle Ψ have significant effects on burr size and edge breakout during the face milling of aluminum-silicon alloys (AlSi9Cu3 and AlSi7Mg). Tripathi and Dornfeld [53] reported the possibility of burr-free conditions when using diamond end mill tools at high cutting speeds. According to [18], the use of sharp cutting edge tools with positive rake angle avoids built-up edge (BUE) formation, thus reducing the burr size.…”
Section: Cutting Tool Geometrymentioning
confidence: 99%